1991
DOI: 10.1007/bf00966697
|View full text |Cite
|
Sign up to set email alerts
|

Decahydroquinoline alkaloids: Noncompetitive blockers for nicotinic acetylcholine receptor-channels in pheochromocytoma cells andTorpedo electroplax

Abstract: In pheochromocytoma PC12 cells, (+)-cis-decahydroquinoline 195A (5-methyl-2-propyl-cis-decahydroquinoline) and (+)-perhydro-cis-decahydroquinoline 219A (2,5-dipropyl-cis-decahydroquinoline) inhibit carbamylcholine-elicited sodium flux with IC50 values of 1.0 and 1.5 microM, respectively. Both of these decahydroquinolines appear to enhance desensitization, although apparent lack of complete removal of (+)-perhydro-cis-219A by washing complicates interpretation of the effects of that agent. A series of cis- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Although lobinaline lacks a pyridyl functional group, the aromatic character of its phenyl substituents in the vicinity of the 1,2-dehydropiperidine functional group may suffice to create a physiochemical environment adequate to engender similar interactions with nicAchRs. The agonist activity lobinaline displays at nicAchRs is of note, given other decahydroquinolines studied to date antagonize nicAchRs, possibly due to the lack of a tetrahydropiperidyl substituent in those previously investigated [100, 101]. Lobinaline has 5 chiral centers, whose stereogenic configuration in the natural molecule from the plant is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although lobinaline lacks a pyridyl functional group, the aromatic character of its phenyl substituents in the vicinity of the 1,2-dehydropiperidine functional group may suffice to create a physiochemical environment adequate to engender similar interactions with nicAchRs. The agonist activity lobinaline displays at nicAchRs is of note, given other decahydroquinolines studied to date antagonize nicAchRs, possibly due to the lack of a tetrahydropiperidyl substituent in those previously investigated [100, 101]. Lobinaline has 5 chiral centers, whose stereogenic configuration in the natural molecule from the plant is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the results showed that compounds 23 afforded better yields (entries 1-5) as compared to compounds 26 (entries 6-10). [17]. Since then, cis-195A (29) has been an attractive and challenging target in organic synthesis because of its intriguing pharmacological properties and unique structure [18].…”
Section: Development Of a Second Generation Palladium-catalyzed Cyclomentioning
confidence: 99%
“…Yet extensive sampling of both lineages over several decades has revealed the presence of hundreds of similar alkaloid toxins [5]. Examples include histrionicotoxins, pumiliotoxins, and decahydroquinolines that target sodium and nicotinic acetylcholine channels in the nervous system [19][20][21]. There is some evidence that toxin autoresistance has also convergently evolved in dendrobatids and mantellids, where similar mutations in the sodium channel pore have been documented and hypothesized to confer alkaloid resistance in these two frog families [22].…”
Section: Introductionmentioning
confidence: 99%